MUSICISTAS MULHERES E SUA INCLUSÃO EM PRÁTICAS DE ARTE NO ENSINO FUNDAMENTAL - FEY, ANDRÉIA SCHACH (2020)
This thesis is engaged in the research line of Education, Culture and Diversity, and was produced from the stance of feminist epistemology to address the problem of androcentrism in art (ARCHER, 2012; PERROT, 2007). The historical and theoretical references pertaining to feminism included Beauvoir (2009), Lauretis (1987), Hollanda (1994), Scott (1995), Crenshaw (2002, 2004), Louro (2008), and Bourdieu (2012). Given the premise of the cultural reproduction of androcentrism as a result of habitus and symbolic violence, an investigation about the visibility of names according to gender was conducted in textbooks for the teaching of Art in Middle School. Four volumes of the collection Por toda Parte (FERRARI et al., 2015) for the 6th, 7th, 8th and 9th grades, which are distributed in Brazilian public schools through the National Program of Didactic Books [Programa Nacional do Livro Didático - PNLD], were analyzed with the objective of verifying whether the repertoires emphasize works by male artists, leading to the underrepresentation of women artists. The occurrences of male and women artists who are mentioned to illustrate contents that pertain to the visual arts, dance, music and theatre were counted in each of the four textbooks. The data was charted and the results of the quantitative and qualitative analysis revealed androcentric repertoires. The repertoire of women artists in the aforementioned textbooks amounted to 11,2% in the 6th grade, 19, 5% in the 7th grade, 11,5% in the 8th grade, and 19,9% in the 8th grade. Given such low occurrence of women artists, and the fact that they are the most underrepresented in music contents, a complementary didactic proposal was produced, so as to increase the repertoire of women musicians and composers. The proposal was devised on the basis of a bibliographic and webographic [sic] search of women artists in timelines that are similar to the art history contents in the selected textbooks. Several hundred composers were found, confirming the existence of works by women that are compatible to the production by males in all the historical periods. Due to the need to narrow the amount of sources, one hundred of them were selected to illustrate the complementary material. The proposal offers resources for art teachers to foster gender inclusion in their pedagogical practices, in addition to allowing for the visibility of musicians who represent ethnic and racial diversity.